Ignition and pusher adiabat. (8th June 2018) - Cheng, B; Kwan, T J T; Wang, Y M; Yi, S A; Batha, S H; Wysocki, F
Abstract: In the last five years, large amounts of high quality data on inertial confinement fusion (ICF) experiments were produced at the National Ignition Facility (NIF). From this data we have significantly advanced our scientific understanding of the physics of thermonuclear (TN) ignition and identified critical issues that must be addressed to achieve a burning hotspot, such as implosion energetics, pusher adiabat, tamping effects, and confinement time. In this paper we present a review of recently developed TN ignition and implosion scaling theory (Cheng et al 2013 Phys. Rev. E88 041101; Cheng et al 2014 Phys. Plasmas 21 10270) that characterizes the thermodynamic properties of the hotspot and the ignition criteria for ICF. We compare our theoretical predictions with NIF data and find good agreement between theory and experiments. We demonstrate the fundamental effects of the pusher adiabat on the energy partition between the cold shell and the hot deuterium–tritium (DT) gas, and thus on the integrated performance of ICF capsules. Theoretical analysis of NIF experiments (Cheng et al 2015 Phys. Plasmas 22 082704; Melvin et al 2015 Phys. Plasmas 22 022708; Cheng et al 2016 Phys. Plasmas 23 120702) and physical explanations of the discrepancies between theory, data, and simulations are presented. It is shown that the true experimental adiabat of the cold DT fuel can be inferred from neutron image data of a capsule implosion. We show that the ablator mix and preheat in the cold fuel can be estimated from the experimentally inferred hotspot mix. Finally, possible paths forward to reach higher yields at NIF implied by the theory are discussed.